Pengaruh Kosentrasi Sari Kunyit Putih (Curcuma Zediaria) Terhadap Kualitas Telur Asin Ditinjau Dari Aktivitas Antioksidan, Total Fenol, Kadar Protein dan Kadar Garam (Jurnal Ilmu dan Teknologi Hasil Ternak, 2015)
The purposes of this research was to determine the effect of Curcuma zedoaria concentrated addition on quality antioxidant activity, total phenols, protein content and salt content of salted egg. The materials were duck’s egg, water, salt, and essence of white turmeric. The method was experiment using Complete Randomized Design (CRD) with five treatments and three for replications. The Curcuma zedoaria juice research were divided into P0 (0%), P1 (10%), P2 (20%), P3 (30%) and P4 (40%). Data was analyzed using Analysis of Variance (ANOVA) and then continued by Duncan’s Multiple Range Test (DMRT), if it was found significant effect among treatmeants. The result showed that the addition of Curcuma zedoaria juice indicated highly significant different effect (P<0.01) on antioxidant activity, protein content and salt content, but significantly effect (P<0.05) on total phenol. The best treatment was the addition of Curcuma zedoaria juice 40% were indicated of antioxidant activity, total phenol, protein content and the salt content was 99.80 mg/g, 0.16%, 9.96%, 2.43% respectively.